The impact of a diabetes management team on the metabolic control and prevalence of complications in paediatric patients with type 1 diabetes mellitus - Kajee, Zaheera (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015